2022
DOI: 10.3389/fnut.2022.1016858
|View full text |Cite
|
Sign up to set email alerts
|

Comparing meat abstainers with avid meat eaters and committed meat reducers

Abstract: Shifting our eating patterns toward less animal-based and more plant-based diets is urgently needed to counter climate change, address public health issues, and protect animal welfare. Although most consumers agree that these are important topics, many consumers are not particularly willing to decrease the meat intensity of their diets. In supporting consumers to shift their diets, it is important to understand consumers’ attitudes, motivations, and preferences related to meat consumption and to take differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 101 publications
3
16
1
Order By: Relevance
“…This may be due to age, gender and education level. Prior studies reported more vegetarians and flexitarians among younger adults36 and highly educated women 37. While 11% of participants identified as vegetarian, a larger proportion may have been flexitarian.…”
Section: Discussionmentioning
confidence: 85%
“…This may be due to age, gender and education level. Prior studies reported more vegetarians and flexitarians among younger adults36 and highly educated women 37. While 11% of participants identified as vegetarian, a larger proportion may have been flexitarian.…”
Section: Discussionmentioning
confidence: 85%
“…It is also important to note that the evaluated sample had a large representation of participants with secondary or higher education. Although it was anticipated that participants with more educational qualifications would have a greater knowledge about the ecological footprint of meat, the results did not show any differences between the groups based on this variable [6, 23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Endorsing this approach, health appears to be the overarching motive for reducing meat consumption as well as maintaining at least some meat consumption ( Latvala et al, 2012 ; de Boer et al, 2017 ; Mylan, 2018 ; Lacroix and Gifford, 2019 ; Malek et al, 2019 ; Sanchez-Sabate et al, 2019 ; Fehér et al, 2020 ; Kemper, 2020 ; Collier et al, 2021 , 2022 ; Kemper and White, 2021 ; Malek and Umberger, 2021a , b ; Verain and Dagevos, 2022 ; Valli et al, 2023 ). Meat is sometimes perceived as an essential food that provides strength and vigour ( de Koning et al, 2015 ; Stoll-Kleemann and Schmidt, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental issues are more important for low-meat eaters, vegetarians and young people; they reinforce those already committed to reducing meat consumption but rarely bring about a change in diet on their own ( de Boer et al, 2017 ; Sanchez-Sabate et al, 2019 ; Fehér et al, 2020 ; Hielkema and Lund, 2021 ; Kemper and White, 2021 ; Malek and Umberger, 2021a ; Trewern et al, 2022 ; Verain and Dagevos, 2022 ; Verain et al, 2022 ; Valli et al, 2023 ). de Boer and Aiking (2021) suggest that pro-environmental food choices are not necessarily motivated by environmental concern but rather result from a complex process involving social motivation, such as being other-oriented and socially responsible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation